Belanja on-line mahasiswa di era pandemi covid-19: modifikasi perilaku konsumen - Prahastiwi Utari; Annisaa Fitri; Eko Setyanto; Chatarina Henny (Islamic Communication Journal, 2020)
The Covid-19 pandemic has changed students consumer behavior from offline to online. The problem in this research is how students’ consumer behavior in online shopping in the era of the Covid-19 pandemic, and the modification of consumer behavior due to regulations and procedures for shopping and buying the products they need. This research is a quantitative study using a survey method. This study is a quantitative research using a survey method. Sampling was done by stratified random sampling, the number of those students FISIP UNS involved as many as 80 people. The results and conclusions of research show that in online shopping, there is a modification of consumer behavior related student needs product, information search, evaluation prior to purchase or an alternative choice, and in the decision to buy or use the product.